2021
DOI: 10.1007/s10856-021-06621-8
|View full text |Cite
|
Sign up to set email alerts
|

Metformin-loaded β-TCP/CTS/SBA-15 composite scaffolds promote alveolar bone regeneration in a rat model of periodontitis

Abstract: Periodontitis is a progressive infectious inflammatory disease, which leads to alveolar bone resorption and loss of periodontal attachment. It is imperative for us to develop a therapeutic scaffold to repair the alveolar bone defect of periodontitis. In this study, we designed a new composite scaffold loading metformin (MET) by using the freeze-drying method, which was composed of β-tricalcium phosphate (β-TCP), chitosan (CTS) and the mesoporous silica (SBA-15). The scaffolds were expected to combine the excel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Tricalcium phosphate (TCP) is a tertiary calcium phosphate, and it is widely used in scaffold-based BTE [ 115 , 116 , 117 ]. TCP is a biodegradable material rich with phosphorus and calcium, and it is commonly used in combination with polymers as a composite scaffold [ 118 ], or drug-loaded material [ 119 ]. However, low biodegradability rate is considered as a drawback of TCP scaffolds.…”
Section: Recent Developments In Bone Tissue Engineeringmentioning
confidence: 99%
“…Tricalcium phosphate (TCP) is a tertiary calcium phosphate, and it is widely used in scaffold-based BTE [ 115 , 116 , 117 ]. TCP is a biodegradable material rich with phosphorus and calcium, and it is commonly used in combination with polymers as a composite scaffold [ 118 ], or drug-loaded material [ 119 ]. However, low biodegradability rate is considered as a drawback of TCP scaffolds.…”
Section: Recent Developments In Bone Tissue Engineeringmentioning
confidence: 99%
“…In a periodontitis rat model, local administration of chitosan-metformin based intra pocket dental film led to the reduction of alveolar bone destruction and displayed good antibacterial activity [ 78 ]. Additionally, the metformin-loaded b-tricalcium phosphate/Chitosan/mesoporous silica scaffolds implanted in the region of alveolar bone malformations in rats suffering from periodontitis promoted alveolar bone regeneration [ 79 ]. In another bone tissue engineering study, the group with metformin plus osteogenic had three- to four-fold increases over those of the osteogenic alone group in osteogenic gene expressions, ALP activity, and mineral synthesis, which demonstrated that human periodontal ligament stem cell (hPDLSCs) was a potent cell source for bone engineering and the calcium phosphate cement (CPC)-metformin scaffold with hPDLSCs was a highly promising construct to promote bone repair and regeneration effectively in craniofacial, dental, and orthopedic applications [ 80 ].…”
Section: Research On Bone Defect Animal Modelsmentioning
confidence: 99%
“…Met is a potent drug that promotes the differentiation of bone marrow mesenchymal stem cells towards osteogenesis. Studies have shown that a β-TCP/CTS/SBA-15 scaffold loaded with Met promotes alveolar bone regeneration in a rat model of periodontitis without cytotoxic effects [4]. The chitosan (CTS) in the scaffold acts as a wound healing agent and the β-tricalcium phosphate (β-TCP) has osteoconductive properties.…”
Section: Research Contents Met With Bone Tissue Regenerationmentioning
confidence: 99%